GIS type zeolite
By optimizing the chemical composition and structure of GIS type zeolite, a GIS type zeolite with high room temperature carbon dioxide adsorption amount and low high temperature adsorption amount was prepared, which solved the problem of insufficient carbon dioxide adsorption ability in the prior art and achieved efficient carbon dioxide separation and recovery.
Patent Information
- Application Number
- CN202180045778.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-31
- Filing Date
- 2021-07-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-07-30
AI Technical Summary
The existing GIS type zeolites have insufficient carbon dioxide adsorption capacity, especially at high temperatures, and have failed to effectively achieve the regeneration of adsorbents and the efficient separation of carbon dioxide.
By optimizing the carbon concentration and silica-alumina ratio of GIS type zeolite and combining with specific X-ray diffraction pattern peak height ratio, a GIS type zeolite with high room temperature carbon dioxide adsorption and low high temperature adsorption were prepared.
The high carbon dioxide adsorption amount near room temperature is achieved, and the adsorption amount of carbon dioxide is reduced during heating, which improves the regeneration efficiency of the adsorbent, and has the potential to be used in the separation and recovery of carbon dioxide in the industry.
Smart Images

Figure CN115996891B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to GIS type zeolite. Background Art
[0002] Zeolite can be used as an adsorbent, a desiccant, a separating agent, a catalyst, a catalyst carrier, a detergent builder, an ion exchanger, a wastewater treatment agent, a fertilizer, a food additive, a cosmetic additive, and the like, and is particularly useful for gas separation.
[0003] Among zeolites, those represented by the GIS structure, which is a code for defining the structure of zeolites established by IZA (International Zeolite Association), are called GIS-type zeolites. GIS-type zeolites are zeolites with fine pores composed of 8-membered oxygen rings. Such GIS-type zeolites are described in, for example, Patent Documents 1 to 4 and Non-Patent Documents 1 to 6.
[0004] Patent Document 1 describes the synthesis of GIS type zeolite for the purpose of effectively utilizing ash residue from coal combustion, and Patent Document 2 describes the formation of a zeolite coating (GIS type zeolite) on the surface of an aluminum plate to improve thermal conductivity.
[0005] In addition, Patent Document 3 discloses that a GIS zeolite with a maximum carbon dioxide adsorption capacity of 52.4 cc / g is obtained by optimizing the crystal structure of GIS zeolite. In addition, Patent Document 4 discloses that a GIS zeolite with a maximum carbon dioxide adsorption capacity of 67.5 cc / g is obtained by changing the peak position of X-ray diffraction, that is, changing the crystal structure.
[0006] Next, non-patent documents 1, 2, and 3 show GIS-type zeolites of silica-alumina. Non-patent document 4 shows GIS-type zeolites of silicoaluminophosphates containing phosphoric acid, which are observed to adsorb carbon dioxide and oxygen, nitrogen, and methane. Non-patent documents 5 and 6 show the silica-alumina ratio (SAR:SiO 2 / Al 2 O 3 GIS-type zeolites having a relatively high silica ratio of 5.0 and 6.9.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 06-340417
[0010] Patent Document 2: Japanese Patent Application No. 2012-519148
[0011] Patent Document 3: International Publication No. 2018 / 110559
[0012] Patent Document 4: International Publication No. 2019 / 202933
[0013] Non-patent literature
[0014] Non-patent document 1: Matthew D. Oleksiak, Arian Ghorbanpour, Marlon T. Conato, B. Peter McGrail, Lars C. Grabow, Radha Kishan Motkuri, Jeffrey D. Rimer "SynthesisStrategies for Ultrastable Zeolite GIS Polymorphs as Sorbents for SelectiveSeparations"Chem.Eur.J.2016,22,16078-16088.
[0015] Non-patent document 2: Pankaj Sharma, Jeong-gu Yeo, Moon Hee Han, Churl Hee Cho "Knobby surfaced, mesoporous, single-phase GIS-NaP1 zeolite microsphere synthesis and characterization for H2 gas adsorption" J.Mater.Chem.A, 2013, 1, 2602-2612.
[0016] Non-patent document 3: Pankaj Sharma, Jeong-gu Yeo, Moon Hee Han, Churl Hee Cho "GIS-NaP1 zeolite microspheres as potentialwater adsorption material: Influence of initial silicaconcentration on adsorptive and physical / topologicalproperties" Sci.Rep.2016,6,1-26.
[0017] Non-patent document 4: Arturo J.Hernandez-Maldonado, Ralph T.Yang, DanielChinn, Curtis L.Munson. "Partially Calcined Gismondine Type SilicoaluminophosphateSAPO-43: Isopropylamine Elimination and Separation of Carbon Dioxide, HydrogenSulfide, and Water" Langmuir 2003, 19, 2193-2200.
[0018] Non-patent document 5: Johann Kecht, B. Mihailova, K. Karaghiosoff, S. Mintova, and Thomas Bein. “Nanosized Gismondine Grown in Colloidal Precursor Solutions” Langmuir 2004, 20, 5271-5276.
[0019] Non-patent document 6: Ulf Hakansson, Lars Falth, Staffan Hansen "Structure of a High-Silica Variety of Zeolite Na-P" Acta Cryst. (1990). C46, 1363-1364. Summary of the invention
[0020] Problems to be solved by the invention
[0021] If attention is paid to the carbon dioxide adsorption capacity of GIS-type zeolite, for example, if carbon dioxide can be removed from exhaust gas from power plants and steel mills, the amount of carbon dioxide emissions can be reduced.
[0022] On the other hand, Patent Documents 1 and 2 do not mention the use of zeolite to adsorb carbon dioxide, and according to the structural analysis results shown in these documents, it cannot be said that the crystal structure required for adsorbing carbon dioxide is clearly formed. In other words, it is believed that the carbon dioxide adsorption capacity of the zeolite described in Patent Documents 1 and 2 is insufficient.
[0023] In the zeolites described in Non-Patent Documents 1 and 2, carbon dioxide adsorption was hardly observed, and separation based on carbon dioxide adsorption or gas permeation was not possible. The main reason for this is believed to be that the 8-membered ring of the GIS type zeolite is deformed to form a long axis of The short axis is The average molecular diameter is The carbon dioxide molecules cannot easily enter the pores.
[0024] Non-Patent Document 3 describes a GIS type zeolite of silicoaluminophosphate. Since the bond distance and bond angle are different from those of silica-alumina, the 8-membered ring pores are slightly larger. Although adsorption of carbon dioxide is observed, the adsorption amount cannot be said to be sufficiently high.
[0025] The zeolite described in Non-Patent Document 4 also cannot be said to be at a sufficient level in terms of the amount of carbon dioxide adsorbed.
[0026] Non-patent documents 5 and 6 do not mention the adsorption performance of carbon dioxide, etc. The inventors analyzed the zeolite synthesized according to the records in these documents. The results showed that no structure suitable for the adsorption of carbon dioxide could be formed in X-ray diffraction, and the carbon dioxide absorption performance of GIS type zeolite could not be exerted.
[0027] In addition, Patent Documents 3 to 4 have obtained GIS-type zeolites with a relatively large amount of carbon dioxide adsorption, but the adsorption amount at high temperature has not been fully studied. Here, when separating and recovering carbon dioxide by a pressure swing adsorption separation method, a temperature swing adsorption separation method, or a pressure swing-temperature swing adsorption separation method using an adsorbent, in addition to the maximum adsorption amount, it is also necessary to desorb and regenerate carbon dioxide by heating or evacuating the adsorbent, and it is also important that the desorption amount of carbon dioxide during regeneration is large.
[0028] As described above, by using an adsorbent that has a large maximum adsorption amount of carbon dioxide when separating carbon dioxide from exhaust gas, etc. (less than 100°C, for example, in a temperature atmosphere of room temperature) and a large desorption amount of carbon dioxide during regeneration (at a high temperature of more than 100°C), when separating and recovering carbon dioxide by a pressure swing adsorption separation method, a temperature swing adsorption separation method, or a pressure swing-temperature swing adsorption separation method, there is a tendency to reduce the required amount of adsorbent, and miniaturization of the adsorption tower can be achieved, which is considered to be economically superior. However, in the prior art such as Patent Documents 1 to 4 and Non-Patent Documents 1 to 6, no adsorbent (zeolite) with such performance has been found.
[0029] The present invention has been made in view of the above circumstances, and its object is to provide carbon dioxide (CO 2 ) and a GIS-type zeolite that adsorbs a large amount of carbon dioxide when heated.
[0030] Means for solving problems
[0031] The present inventors have repeatedly conducted intensive studies to solve the above-mentioned problems and have found that the problems can be solved when the carbon concentration and the silicon oxide-alumina ratio of the GIS type zeolite are within a prescribed range and when the height ratio of a specific diffraction peak in the diffraction pattern obtained by X-ray diffraction measurement is within a prescribed range of values, thereby achieving the present invention.
[0032] That is, the present invention is as follows. [1]
[0034] A GIS type zeolite having a carbon atom content of 4 mass % or less and a silica-alumina ratio of 4.23 or more, wherein:
[0035] In the spectrum obtained by X-ray diffraction, at least one of the following conditions (i) and (ii) is satisfied.
[0036] (i) When the peak heights near 2θ=12.45° and 2θ=28.07° are defined as A and B, respectively, 0.62≤A / B;
[0037] (ii) When the peak heights near 2θ=28.07° and near 2θ=46.04° are defined as B and C, respectively, 11.5≤B / C. [2]
[0039] The GIS type zeolite as described in [1] comprises silica-alumina. [3]
[0041] The GIS-type zeolite as described in [1] or [2] contains H and an alkali metal element as counter cations. [4]
[0043] An adsorbent comprising the GIS-type zeolite according to any one of [1] to [3]. [5]
[0045] A separation method, wherein the adsorbent described in [4] is used to separate a 2 、N 2 , O 2 , Ar, CO and hydrocarbons, and a mixture of at least two gases selected from the group consisting of CO 2 , H 2 O, He, Ne, Cl 2 NH 3 and HCl. [6]
[0047] The separation method as described in [5], wherein the above-mentioned gas separation is carried out by pressure swing adsorption separation method, temperature swing adsorption separation method or pressure swing-temperature swing adsorption separation method. [7]
[0049] A method for producing a purified gas, wherein the adsorbent described in [4] is used to produce a purified gas selected from the group consisting of H 2 、N 2 , O 2 , Ar, CO and hydrocarbons, and a mixture of at least two gases selected from the group consisting of CO 2 , H 2 O, He, Ne, Cl 2 NH 3 and HCl. [8]
[0051] A method for producing GIS type zeolite, comprising the following steps:
[0052] A process for preparing a mixed gel, the mixed gel comprising a silicon oxide source containing silicon, an aluminum source containing aluminum, an alkali source containing at least one selected from an alkali metal (M1) and an alkaline earth metal (M2), a phosphorus source containing phosphorus, and water; and
[0053] The hydrothermal synthesis step is to hydrothermally synthesize the mixed gel at a temperature of 80°C to 145°C.
[0054] In the mixed gel obtained in the above preparation step, SiO 2 / Al 2 O 3 is 3.0 or more and 70.0 or less, and (M1 2 O+M2O) / Al 2 O 3 is less than 15.0, and H 2 O / OH - 95 or above and 480 or below,
[0055] In the above GIS type zeolite, the carbon atom content is 4 mass % or less, and the silica-alumina ratio is 4.23 or more.
[0056] Effects of the Invention
[0057] According to the present invention, carbon dioxide (CO) can be provided near room temperature. 2 ) and a GIS-type zeolite that adsorbs a large amount of carbon dioxide when heated. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1This is an X-ray diffraction (XRD) chart of the GIS-type zeolite obtained in Example 1.
[0059] Figure 2 This is a diagram illustrating an adsorbent according to one embodiment of the present invention. DETAILED DESCRIPTION
[0060] A specific embodiment of the present invention (hereinafter referred to as "this embodiment") will be described in detail below. The present invention is not limited to the following description, and can be implemented with various modifications within the scope of the gist thereof.
[0061] The GIS type zeolite of the first aspect of the present embodiment (hereinafter also referred to as "first GIS type zeolite") is a GIS type zeolite having a carbon atom content of 4 mass % or less and a silica-alumina ratio of 4.23 or more, wherein the following condition (i) is satisfied in the spectrum obtained by X-ray diffraction:
[0062] (i) When the peak heights near 2θ=12.45° and near 28.07° are denoted as A and B, respectively, 0.62≤A / B.
[0063] In addition, the GIS type zeolite of the second aspect of the present embodiment (hereinafter also referred to as "second GIS type zeolite") is a GIS type zeolite having a carbon atom content of 4 mass% or less and a silica-alumina ratio of 4.23 or more, wherein the following condition (ii) is satisfied in the spectrum obtained by X-ray diffraction:
[0064] (ii) When the peak heights near 2θ=28.07° and near 46.04° are defined as B and C, respectively, 11.5≤B / C.
[0065] Hereinafter, unless otherwise stated, the term "GIS type zeolite according to the present embodiment" includes the first GIS type zeolite and the second GIS type zeolite.
[0066] That is, the GIS type zeolite of the present embodiment is a GIS type zeolite having a carbon atom content of 4 mass % or less and a silica-alumina ratio of 4.23 or more, and satisfies at least one of the following conditions (i) and (ii) in the spectrum obtained by X-ray diffraction:
[0067] (i) When the peak heights near 2θ=12.45° and near 28.07° are defined as A and B, respectively, 0.62≤A / B;
[0068] (ii) When the peak heights near 2θ=28.07° and near 46.04° are defined as B and C, respectively, 11.5≤B / C.
[0069] Since the GIS type zeolite of this embodiment is constructed as described above, the amount of carbon dioxide adsorbed near room temperature is large, and the amount of carbon dioxide adsorbed when heated is small. In the GIS type zeolite having such characteristics, the amount of carbon dioxide desorbed when heated and regenerated after carbon dioxide adsorption is large, and carbon dioxide can be effectively recovered.
[0070] It should be noted that in the GIS-type zeolite of this embodiment, an 8-membered ring structure is clearly formed, which can fully adsorb carbon dioxide, and by achieving an appropriate silica-alumina ratio, the hydrophilicity, i.e., polarity, is reduced, and the adsorption force of carbon dioxide is also moderately reduced. Therefore, it is believed that the amount of carbon dioxide desorbed during heating regeneration increases.
[0071] The silicon oxide-alumina ratio (SiO 2 / Al 2 O 3 The calculated molar ratio, hereinafter also referred to as "SAR") is 4.23 or more. The lower the SAR of the zeolite, the more hydrophilic it is, and the stronger the adsorption force of polar molecules such as carbon dioxide. In order to make the adsorption force have an appropriate strength and desorb by heating or vacuuming, the SAR is preferably high. From the above aspects, the SAR is preferably above 4.40, more preferably above 4.80. On the other hand, by ensuring the alumina content to a certain extent, the adsorption force of carbon dioxide is increased, and there is a tendency to fully increase the amount of carbon dioxide adsorption at room temperature, so the SAR is preferably below 30, more preferably below 20, and further preferably below 15.
[0072] The SAR can be measured by the method described in the examples below. The SAR can be adjusted to the above range by adjusting the composition ratio of the mixed gel used for the synthesis of the GIS type zeolite to the preferred range described below.
[0073] In the GIS type zeolite of this embodiment, an organic structure directing agent can be used during synthesis. Since the organic structure directing agent will remain in the pores and fill the space entered by carbon dioxide, the adsorption amount of carbon dioxide will be reduced, so it is preferred to adjust the amount used. The quantification of the organic structure directing agent or the modified substance thereof can be performed by measuring the carbon atom weight. From the above aspect, the carbon atom content is 4% by mass or less, preferably 3% by mass or less, and more preferably 2% by mass or less.
[0074] The carbon atom content can be measured by the method described in the examples below. The carbon atom content can be adjusted to the above range by adjusting the composition ratio of the mixed gel used in the synthesis of the GIS type zeolite to the preferred range described below.
[0075] In the present embodiment, from the viewpoint of further improving the selective adsorption capacity of carbon dioxide, the GIS type zeolite preferably contains silica-alumina.
[0076] In addition, in the GIS type zeolite of this embodiment, it is preferable that silicon oxide and aluminum oxide are main components (80 mass % or more). The main component refers to a component accounting for 80 mass % or more.
[0077] The aluminum content in the GIS-type zeolite of the present embodiment is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more. The upper limit of the aluminum content is not particularly limited as long as the SAR satisfies the above-mentioned prescribed range, and is determined by the silicon oxide content and the SAR value.
[0078] The silicon content in the GIS-type zeolite of the present embodiment is preferably 3% by mass or more, more preferably 5% by mass or more. The upper limit of the silicon content is not particularly limited as long as SAR satisfies the above-mentioned prescribed range, and is determined based on the alumina content and SAR value.
[0079] The phosphorus content in the GIS-type zeolite of the present embodiment is preferably 4% by mass or less. The lower limit of the phosphorus content is not particularly limited, and may be 0% by mass or more.
[0080] The Zr content in the GIS-type zeolite of the present embodiment is preferably 8% by mass or less. The lower limit of the Zr content is not particularly limited, and may be 0% by mass or more.
[0081] The Ti content in the GIS-type zeolite of the present embodiment is preferably 8% by mass or less. The lower limit of the Ti content is not particularly limited, and may be 0% by mass or more.
[0082] From the viewpoint of further improving the selective adsorption capacity of carbon dioxide, the phosphorus atom content in the GIS-type zeolite of the present embodiment is more preferably 1.5% by mass or less, and particularly preferably 0% by mass.
[0083] The contents of aluminum, silicon, phosphorus, Zr and Ti can be measured by the methods described in the examples below. The contents of aluminum, silicon, phosphorus, Zr and Ti can be adjusted to the above ranges by adjusting the composition ratio of the mixed gel used in the synthesis of the GIS type zeolite to the preferred ranges described below.
[0084] (X-ray diffraction peak)
[0085] Regarding the first GIS type zeolite, in the spectrum obtained by X-ray diffraction, (i) when the peak heights near 2θ=12.45° and near 28.07° are respectively defined as A and B, 0.62≤A / B is satisfied. The peak near 2θ=12.45° is typically observed in the range of 12.30° or more and less than 12.55°, and the peak near 2θ=28.07° is typically observed in the range of 2θ=27.82° or more and less than 28.32°.
[0086] In the X-ray diffraction peaks of the GIS type zeolite of the present embodiment at 25°C, the peaks near 2θ=12.45° and near 28.07° are the diffraction peaks of (1 0 1) and (3 0 1), respectively. The diffraction peak of (1 0 1) is a diffraction reflecting the periodic structure of the oxygen 8-membered ring of the GIS type zeolite, and the diffraction peak of (3 0 1) is a diffraction reflecting the periodic structure of the 0.3176nm period, which is equivalent to the period formed by the unit structure of silicon oxide in the zeolite, that is, O-Si-O. When the heights of the diffraction peaks of (1 0 1) and (3 0 1) are respectively set as A and B, the case where A / B is large indicates that, based on the basic structure of silicon oxide in the zeolite, a larger periodic structure, that is, a structure containing an 8-membered ring structure, is clear. By clearly forming the 8-membered ring structure, a pore structure having a space that can enclose gas molecules can be formed, and a molecular sieving effect can be obtained in which only molecules smaller than carbon dioxide enter the pores. That is, it is considered that even a GIS-type zeolite having a high SAR has a large number of spaces capable of storing carbon dioxide at around room temperature and can have a high carbon dioxide adsorption capacity at around room temperature.
[0087] From the above viewpoints, the value of A / B is preferably 0.63 or more, and more preferably 0.68 or more. The upper limit of the value of A / B is not particularly limited, and may be, for example, 2.00 or less.
[0088] In addition, from the same viewpoint as above, the second GIS-type zeolite described below can further satisfy the above range.
[0089] Regarding the second GIS type zeolite, in the spectrum obtained by X-ray diffraction, (ii) when the peak heights near 2θ=28.07° and near 46.04° are respectively defined as B and C, 11.5≤B / C is satisfied. The peak near 2θ=46.04° is typically a diffraction peak of (5 0 1) observed in the range of 45.64° or more and less than 46.46°, reflecting a finer structure than the peak of (3 0 1).
[0090] When B / C is large, it means that the O-Si-O unit structure of silicon oxide in the zeolite is formed without defects based on a finer periodic structure, which means that there are fewer pores on the wall of the space formed by the 8-membered ring structure that can enclose carbon dioxide, through which carbon dioxide can escape. Even when the SAR is high and the adsorption force of carbon dioxide is reduced, the carbon dioxide adsorbed in the pores can be retained, and it is considered that the adsorption amount of carbon dioxide can be maintained.
[0091] From the above viewpoints, the value of B / C is preferably 12.8 or more, and more preferably 15.7 or more. The upper limit of the value of B / C is not particularly limited, and may be, for example, 35.0 or less.
[0092] From the same viewpoint as above, the first GIS-type zeolite can further satisfy the above range.
[0093] It should be noted that the above-mentioned values of A / B and B / C can be measured by the method described in the examples described later, and can be adjusted to the above-mentioned ranges by adjusting the composition ratio of the mixed gel, the aging time of the mixed gel, the conditions during the hydrothermal synthesis (heating temperature, heating time), etc. to the preferred ranges described later.
[0094] In the spectrum obtained by X-ray diffraction, GIS type zeolite has peaks near 2θ=12.45°, 28.07°, and 46.04°. 2 The effective adsorption capacity of CO tends to be improved. In the GIS type zeolite of this embodiment, by satisfying at least one of the above conditions (i) and (ii), CO 2 It should be noted that the effective adsorption capacity of the GIS type zeolite in this embodiment is calculated by the CO 2 Saturated adsorption capacity and CO at 180℃ 2 The amount of adsorption can be defined as the difference between the saturated adsorption amount and the saturated adsorption amount, and can be measured by the method described in the examples described later.
[0095] The larger the effective adsorption capacity in this embodiment, the more it can reduce, for example, CO 2 The amount of adsorbent required for separation and recovery can reduce the amount of equipment such as adsorption towers.
[0096] From the above aspects, the effective adsorption capacity in the present embodiment is preferably 42cc / g or more, more preferably 45cc / g or more, and further preferably 48cc / g or more. The upper limit of the effective adsorption capacity in the present embodiment is not particularly limited, for example, it can be 180cc / g or less. It should be noted that the method for determining the effective adsorption capacity is based on the method described in the examples.
[0097] The peak half-width obtained by X-ray diffraction indicates the crystallinity of the lattice plane where the diffraction occurs, and the half-width is preferably narrow. In the spectrum obtained by X-ray diffraction of the GIS type zeolite of the present embodiment, the peak half-width near 2θ=12.45° is preferably 0.45deg or less, more preferably 0.40deg or less, and further preferably 0.35deg or less. In addition, from the same aspect, in the spectrum obtained by X-ray diffraction of the GIS type zeolite of the present embodiment, the peak half-width near 2θ=28.07° is preferably 0.80deg or less, more preferably 0.70deg or less, and further preferably 0.60deg or less. In addition, from the same aspect, in the spectrum obtained by X-ray diffraction of the GIS type zeolite of the present embodiment, the peak half-width near 2θ=46.04° is preferably 0.95deg or less, more preferably 0.85deg or less, and further preferably 0.75deg or less.
[0098] It is presumed that the structure of the GIS zeolite suggested by the peak half width described above does not cause loss of carbon dioxide adsorption sites and reduces desorption of carbon dioxide due to loss of pore walls, thereby maintaining a high carbon dioxide adsorption amount.
[0099] The peak half width values can be adjusted to the above ranges by adjusting the composition ratio of the mixed gel, the aging time of the mixed gel, the conditions during the hydrothermal synthesis (heating temperature, heating time), etc. to the preferred ranges described below.
[0100] The GIS type zeolite of the present embodiment may contain H and an alkali metal element as a counter cation. Examples of the alkali metal element include lithium, sodium, potassium, rubidium, and cesium. Among these, alkali metal elements are preferred.
[0101] In the GIS type zeolite of the present embodiment, from the aspect of maintaining the 8-membered ring elliptical structure of the GIS type zeolite, the content of the alkali metal element in the GIS type zeolite is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and further preferably 0.6% by mass or more relative to the total amount of the GIS type zeolite. On the other hand, from the aspect of preventing the generation of impurities and preventing the decrease in the crystallinity of the GIS type zeolite, the content of the alkali metal element in the GIS type zeolite is preferably 35% by mass or less, more preferably 34% by mass or less, and further preferably 33% by mass or less.
[0102] The content of the counter cation can be measured by the method described in the examples below, and can be adjusted to the above range by, for example, adjusting the composition ratio of the mixed gel to the preferred range described below.
[0103] Among the above-mentioned alkali metal elements, sodium is more preferable.
[0104] In this embodiment, from the perspective of maintaining the 8-membered ring elliptical structure of the GIS zeolite, the sodium content in the GIS zeolite is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.6% by mass or more relative to the total amount of the GIS zeolite. On the other hand, from the perspective of preventing the formation of impurities and preventing the crystallinity of the GIS zeolite from being reduced, the sodium content in the GIS zeolite is preferably 35% by mass or less, more preferably 34% by mass or less, and even more preferably 33% by mass or less.
[0105] (Manufacturing method)
[0106] The method for producing the GIS zeolite of the present embodiment is not particularly limited, and may include, for example, a step of preparing a mixed gel, wherein the mixed gel contains a silicon oxide source containing silicon, an aluminum source containing aluminum, an alkali source containing at least one selected from an alkali metal (M1) and an alkaline earth metal (M2), a phosphorus source containing phosphorus, and water. The method for producing the GIS zeolite of the present embodiment more specifically includes the following steps: a step of preparing a mixed gel, wherein the mixed gel contains a silicon oxide source containing silicon, an aluminum source containing aluminum, an alkali source containing at least one selected from an alkali metal (M1) and an alkaline earth metal (M2), a phosphorus source containing phosphorus, and water; and a hydrothermal synthesis step of hydrothermally synthesizing the mixed gel at a temperature of 80°C to 145°C, wherein SiO 2 / Al 2 O 3 3.0 or more and 70.0 or less, and (M1 2 O+M2O) / Al 2 O 3 is less than 15.0, and H 2 O / OH - The GIS type zeolite has a carbon atom content of 4 mass % or less and a silica-alumina ratio of 4.23 or more.
[0107] First, the mixed gel and the components contained therein will be described below.
[0108] [Mixed gel]
[0109] The mixed gel in this embodiment is a mixture containing a silicon oxide source, an aluminum source, an alkali source, and water as components. The mixed gel may also contain a phosphorus source and an organic structure-directing agent, but preferably in as small a amount as possible.
[0110] The silicon oxide source refers to a component in the mixed gel that is a raw material of silicon contained in the zeolite manufactured from the mixed gel, the aluminum source refers to a component in the mixed gel that is a raw material of aluminum contained in the zeolite manufactured from the mixed gel, the alkali source refers to a component in the mixed gel that is a raw material of alkali metal and / or alkaline earth metal contained in the zeolite manufactured from the mixed gel, and the phosphorus source refers to a component in the mixed gel that is a raw material of phosphorus contained in the zeolite manufactured from the mixed gel.
[0111] [Silicon oxide source]
[0112] The silicon oxide source is not particularly limited as long as it is a commonly used silicon oxide source. Specific examples include sodium silicate, amorphous silicon oxide, colloidal silicon oxide, wet process silicon oxide, dry process silicon oxide, silica gel, amorphous aluminum silicate gel, tetraethoxysilane (TEOS), trimethylethoxysilane, etc. These compounds can be used alone or in combination. Here, the amorphous aluminum silicate gel is a silicon oxide source and also an aluminum source.
[0113] Among these, sodium silicate is preferred because it tends to provide zeolite with high crystallinity.
[0114] [Aluminum source]
[0115] The aluminum source is not particularly limited as long as it is a commonly used aluminum source, and specific examples thereof include sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum acetate, aluminum hydroxide, aluminum oxide, aluminum chloride, aluminum alkoxide, metallic aluminum, amorphous aluminum silicate gel, etc. These compounds may be used alone or in combination of a plurality of them.
[0116] Among these, sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum acetate, aluminum hydroxide, aluminum chloride, and aluminum alkoxide are preferred because they tend to produce zeolites with high crystallinity. From the same perspective, sodium aluminate and aluminum hydroxide are more preferred, and sodium aluminate is further preferred.
[0117] [Alkali source]
[0118] The type of the base in the alkali source is not particularly limited, and any alkali metal compound and / or any alkaline earth metal compound can be used.
[0119] Examples of the alkaline source include, but are not limited to, hydroxides, bicarbonates, carbonates, acetates, sulfates, nitrates, etc. of alkali metals or alkaline earth metals. These compounds may be used alone or in combination of plural types.
[0120] As the alkali metal and alkaline earth metal used as the alkali source, Li, Na, K, Rb, Cs, Ca, Mg, Sr, Ba, etc. can be generally used. From the aspect that the crystallization formation of the GIS type skeleton becomes easier, Na and K are preferred, and Na is more preferred. In addition, the alkali metal and alkaline earth metal used as the alkali source can be used alone or in combination of a plurality of them.
[0121] Specifically, the alkali source includes, but is not limited to, sodium hydroxide, sodium acetate, sodium sulfate, sodium nitrate, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium acetate, potassium sulfate, potassium nitrate, potassium carbonate, potassium bicarbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium nitrate, lithium carbonate, lithium bicarbonate, rubidium hydroxide, rubidium acetate, rubidium sulfate, rubidium nitrate, rubidium carbonate, rubidium bicarbonate, cesium hydroxide, cesium acetate, cesium sulfate, cesium nitrate, cesium carbonate, cesium bicarbonate, calcium hydroxide, calcium acetate, calcium sulfate, calcium nitrate, calcium carbonate, calcium bicarbonate, magnesium hydroxide, magnesium acetate, magnesium sulfate, magnesium nitrate, magnesium carbonate, magnesium bicarbonate, strontium hydroxide, strontium acetate, strontium sulfate, strontium nitrate, strontium carbonate, strontium bicarbonate, barium hydroxide, barium acetate, barium sulfate, barium nitrate, barium carbonate, barium bicarbonate, etc.
[0122] Among these, sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, cesium hydroxide, calcium hydroxide, magnesium hydroxide, strontium hydroxide, and barium hydroxide are preferred; sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, and cesium hydroxide are more preferred; and sodium hydroxide is further preferred.
[0123] [Phosphorus source]
[0124] The phosphorus source is not particularly limited as long as it is a commonly used phosphorus source, and specific examples include aqueous phosphoric acid solution, sodium phosphate, aluminum phosphate, potassium phosphate, lithium phosphate, calcium phosphate, barium phosphate, etc. These compounds may be used alone or in combination of plural types.
[0125] Among these, aqueous phosphoric acid solution, sodium phosphate, and aluminum phosphate are preferred because they tend to produce zeolite with high crystallinity. From the same viewpoint, aqueous phosphoric acid solution and sodium phosphate are more preferred, and aqueous phosphoric acid solution is still more preferred.
[0126] [Organic structure directing agent]
[0127] When the mixed gel is hydrothermally synthesized to produce zeolite, the organic structure-directing agent is a compound that promotes crystallization into a zeolite structure. The organic structure-directing agent may be used as necessary in the crystallization of zeolite.
[0128] The organic structure directing agent may be of any type as long as it can form the desired GIS-type zeolite. The organic structure directing agent may be used alone or in combination of two or more.
[0129] As organic structure directing agents, for example, amines, quaternary ammonium salts, alcohols, ethers, amides, alkyl ureas, alkyl thioureas, cyanoalkanes, and alicyclic heterocyclic compounds containing nitrogen as a heteroatom can be used, but are not limited thereto. Preferably, alkylamines are used, and more preferably, isopropylamine is used.
[0130] Such salts are accompanied by anions. Representative of such anions include, but are not limited to, Cl - Br - ,I - Halogen ions, hydroxide ions, acetate ions, sulfate ions, nitrate ions, carbonate ions, and bicarbonate ions are preferred. Among these, halogen ions and hydroxide ions are preferred, and halogen ions are more preferred, because crystal formation of the GIS-type skeleton becomes easier.
[0131] [Composition ratio of mixed gel]
[0132] In this embodiment, in order to synthesize a GIS-type zeolite having an appropriate SAR and an appropriate structure, the ratio of the aluminum source to water in the mixed gel and the OH - The ratio of aluminum source to water in the mixed gel is preferably within an appropriate range. 2 O 3 The molar ratio of H 2 O / Al 2 O 3 The OH in the mixed gel - The ratio of water to OH - The molar ratio of H 2 O / OH - expressed in the form of .
[0133] OH - OH - It is derived from NaOH, Ca(OH) 2 The amount of OH in the feed of inorganic hydroxides such as tetraethylammonium hydroxide and organic hydroxides such as tetraethylammonium hydroxide - , such as sodium aluminate or sodium silicate, which are oxides, or OH released when their hydrates are dissolved in water - Not included. In the formation of zeolite, as the silicon oxide source, aluminum source, and alkali source dissolved in the water solvent undergo a crystallization reaction, a portion of them dissolves into the alkaline solvent, resulting in a balance between crystallization and redissolution. 2 OH of inorganic hydroxides such as tetraethylammonium hydroxide or organic hydroxides such as tetraethylammonium hydroxide -Adding OH to the mixed gel means that the balance between crystallization and redissolution is biased towards redissolution. In redissolution, the amorphous or low-crystalline part dissolves first. Therefore, by appropriately increasing the OH - The incompletely crystallized part is dissolved again and crystallized again repeatedly, which can increase the formation of the ideal crystal structure. - , excessive dissolution will occur, and there is a tendency that no crystals can be obtained, or other crystal phases, such as ANA type zeolite with a more stable structure, will be generated. In addition, the dissolved alumina is more reactive than silica, and alumina is easily incorporated into the crystals. Therefore, by appropriately adjusting the OH - The speed of crystallization and redissolution can be adjusted, and the ratio of silicon oxide to aluminum oxide incorporated into the crystals can be optimized, so that the SAR of the synthesized GIS-type zeolite can be optimized.
[0134] If the water ratio (H 2 O / Al 2 O 3 ) is high, the components in the mixed gel are more easily dispersed uniformly; however, if it is too high, the crystallization rate tends to be significantly reduced. Therefore, in order to synthesize GIS-type zeolite with the best SAR and the best crystal structure, it is preferred to perform H 2 O / OH - While controlling H 2 O / Al 2 O 3 Control at its best.
[0135] Based on the above aspects, H 2 O / Al 2 O 3 and H 2 O / OH - Preferably 250≤H 2 O / Al 2 O 3 ≤780 and 95≤H 2 O / OH - ≤480, more preferably 260≤H 2 O / Al 2 O 3 ≤778 and 98≤H 2 O / OH - ≤475, more preferably 270≤H 2 O / Al 2 O 3 ≤775 and 100≤H 2 O / OH - ≤472.
[0136] The ratio of the silicon oxide source to the aluminum source in the mixed gel is the molar ratio of the oxides of each element, i.e., SiO 2 / Al 2 O 3 It should be noted that the ratio of the synthesized zeolite is not consistent with the silica-alumina ratio of the mixed gel. The silica-alumina ratio of the synthesized zeolite is determined by other compositions and synthesis conditions.
[0137] The SiO in the hybrid gel 2 / Al 2 O 3 The ratio is not particularly limited as long as it can form zeolite, but is preferably 3.0 to 70.0, more preferably 3.5 to 65.0, and even more preferably 4.0 to 60.0, because it tends to suppress the formation of zeolite having a framework different from a GIS-type framework.
[0138] The ratio of aluminum source to alkali source in the mixed gel is M1 2 The total amount of O and M2O relative to Al 2 O 3 The molar ratio, i.e. (M1 2 O+M2O) / Al 2 O 3 (Here, M1 represents an alkali metal and M2 represents an alkaline earth metal. They are calculated in the form of oxides.) It should be noted that from the perspective of making it easier to crystallize the GIS-type skeleton, the (M1 2 O+M2O) / Al 2 O 3 It is preferably 1.5 or more, more preferably 1.6 or more, and further preferably 1.65.
[0139] From the perspective of being able to suppress the formation of zeolite having a framework different from the GIS-type framework, (M1 2 O+M2O) / Al 2 O 3 It is preferably 15.0 or less, more preferably 12.0 or less, and even more preferably 10.0 or less.
[0140] The ratio of phosphorus source to aluminum source in the mixed gel is based on the molar ratio of the oxides of each element, i.e., P 2 O 5 / Al 2 O 3 expressed in the form of .
[0141] The P 2 O 5 / Al 2 O 3The ratio is not particularly limited as long as it can form zeolite, but is preferably less than 1.0, more preferably 0.6 or less, further preferably 0.4 or less, and particularly preferably 0, because it tends to suppress the formation of zeolite having a framework different from a GIS-type framework.
[0142] When the mixed gel contains an organic structure directing agent, the ratio of the aluminum source to the organic structure directing agent in the mixed gel is expressed as: 2 O 3 The molar ratio of R / Al 2 O 3 It is expressed in the form of (here R represents an organic structure directing agent). From the perspective of making the crystal formation of the GIS-type skeleton easier and / or shortening the synthesis time, and the excellent economy in manufacturing the zeolite, it is preferably less than 7.0, more preferably less than 6.0, and further preferably less than 5.0. When an organic structure directing agent is used, the organic structure directing agent remains in the pores of the zeolite, carbon dioxide does not enter the pores, and the adsorption amount is reduced. In order to remove the organic structure directing agent, it is necessary to heat to at least 400°C, but the GIS-type zeolite will undergo crystal fragmentation and become amorphous at above 350°C, so it is preferably less organic structure directing agent. From this perspective, R / Al is preferably 2 O 3 It is 4.0 or less, more preferably 2.0 or less, and further preferably 0.1 or less.
[0143] As described above, the method for producing GIS type zeolite of the present embodiment includes a step of preparing a mixed gel, wherein the mixed gel contains a silicon oxide source containing silicon, an aluminum source containing aluminum, an alkali source containing at least one selected from an alkali metal (M1) and an alkaline earth metal (M2), a phosphorus source, and water, wherein the molar ratio of each component in the mixed gel is preferably calculated in the form of oxides of each element with respect to the silicon, aluminum, alkali metal (M1) and alkaline earth metal (M2), and phosphorus source, and the following formulas (1), (2), (3), (4), and (5) are preferably used. The molar ratios α, β, γ, δ, and ε shown satisfy 3.0≤α≤70.0, 1.5≤β≤15.0, 0≤γ<1.0, 250≤δ≤780, and 95≤ε≤480, more preferably 3.5≤α≤65.0, 1.6≤β≤12.0, 0≤γ<0.6, 260≤δ≤778, and 98≤ε≤475, and further preferably 4.0≤α≤60.0, 1.65≤β≤10.0, 0≤γ<0.4, 270≤δ≤775, and 100≤ε≤472. The GIS type zeolite of this embodiment is particularly preferably obtained by the above-mentioned production method.
[0144] α=SiO 2 / Al 2 O 3 (1)
[0145] β=(M1 2 O+M2O) / Al 2 O 3 (2)
[0146] γ=P 2 O 5 / Al 2 O 3 (3)
[0147] δ=H 2 O / Al 2 O 3 (4)
[0148] ε=H 2 O / OH - (5)
[0149] In the method for producing GIS-type zeolite of the present embodiment, it is preferred that the molar ratios α, β, γ, δ, and ε satisfy the above ranges, and when the mixed gel further contains an organic structure directing agent R, the molar ratio ε represented by the following formula (6) satisfies ζ≤4.
[0150] ζ=R / Al 2 O 3 (6)
[0151] The mixed gel does not necessarily need to contain seed crystals, but a previously produced GIS type zeolite may be added as seed crystals to the mixed gel to obtain the GIS type zeolite of the present embodiment.
[0152] [Hybrid Gel Preparation Process]
[0153] The preparation process of the mixed gel is not particularly limited, and may include, for example, a mixing process of mixing a silicon oxide source, an aluminum source, an alkali source, water, and, if necessary, an organic structure directing agent at one time or in multiple stages; and a aging process of the mixture obtained in the mixing process.
[0154] In the mixing step, the components including the silicon oxide source, the aluminum source, the alkali source, water, and, if necessary, the organic structure-directing agent may be mixed at once or in multiple stages.
[0155] The order of mixing in multiple stages is not limited and can be appropriately selected according to the conditions used. When mixing in multiple stages, it can be carried out with or without stirring.
[0156] When stirring is performed, there is no particular limitation as long as it is a stirring method commonly used, and specific examples thereof include methods using paddle stirring, vibration stirring, swing stirring, centrifugal stirring, and the like.
[0157] The rotation speed of stirring is not particularly limited as long as it is a stirring speed generally used, and for example, it may be 1 rpm or more and less than 2000 rpm.
[0158] The temperature in the mixing step is not particularly limited as long as it is a temperature generally used, and for example, it may be -20°C or higher and lower than 80°C.
[0159] The time of the mixing step is not particularly limited and can be appropriately selected according to the temperature of the mixing step. For example, it can be greater than 0 minutes and 1000 hours or less.
[0160] The aging process can be carried out under static or stirring conditions.
[0161] When stirring is performed in the aging step, there is no particular limitation as long as the stirring method is generally used, and specific examples thereof include methods using paddle stirring, vibration stirring, swing stirring, centrifugal stirring, and the like.
[0162] The rotation speed of stirring is not particularly limited as long as it is a stirring speed generally used, and for example, it may be 1 rpm or more and less than 2000 rpm.
[0163] The temperature of the aging step is not particularly limited as long as it is a temperature generally used, and for example, it may be -20°C or higher and lower than 80°C.
[0164] The time of the aging step is not particularly limited and can be appropriately selected according to the temperature of the aging step. For example, it can be greater than 0 minutes and 1000 hours or less.
[0165] It is believed that zeolite produces the dissolution of raw materials, the generation and redissolution of zeolite precursors in the mixing process and the aging process of raw materials. In order to form a large periodic structure containing 8-membered rings without generating defects, it is preferred not to excessively form the zeolite precursor. In addition, in the case of excessively forming the precursor of zeolite, the generation of ANA type zeolite, which is a more stable structure, tends to increase, so it is also preferred not to over-mature. On the other hand, it is preferred that the raw materials are fully mixed and the raw material gel is in a uniform state. Regarding the time for the mixing process and the aging process to be combined, as long as it is appropriately adjusted based on the composition of the raw materials to obtain a zeolite of an appropriate structure, there is no particular limitation. The above time is representatively preferably more than 1 minute and less than 24 hours, more preferably more than 3 minutes and less than 23 hours, further preferably more than 10 minutes and less than 18 hours, further preferably more than 12 minutes and less than 15 hours, and more preferably more than 20 minutes and less than 6 hours.
[0166] [Hydrothermal synthesis process]
[0167] The method for producing GIS-type zeolite of the present embodiment preferably further comprises a hydrothermal synthesis step at a hydrothermal synthesis temperature of 80° C. to 145° C., and the hydrothermal synthesis temperature is more preferably 80° C. to 140° C. That is, the mixed gel obtained by the preparation step is preferably subjected to hydrothermal synthesis by being kept at a predetermined temperature for a predetermined time in a stirring or static state.
[0168] The temperature of the hydrothermal synthesis is not particularly limited as long as it is a temperature commonly used, but is preferably 80° C. or higher from the perspective of shortening the synthesis time and achieving excellent economic efficiency in zeolite production. From the perspective of being able to suppress the formation of zeolites having a framework different from the GIS-type framework, it is more preferably 90° C. or higher, and even more preferably 100° C. or higher.
[0169] From the viewpoint of being able to suppress the formation of zeolite having a framework different from the GIS-type framework, the temperature is more preferably 145° C. or lower, further preferably 140° C. or lower, and further preferably 135° C. or lower.
[0170] The temperature of the hydrothermal synthesis can be constant or can be changed in stages.
[0171] The time for the hydrothermal synthesis is not particularly limited as long as it is a time generally used, and can be appropriately selected according to the temperature for the hydrothermal synthesis.
[0172] The time for the hydrothermal synthesis is preferably 3 hours or longer, more preferably 10 hours or longer, from the viewpoint of forming a GIS skeleton, and further preferably 24 hours or longer from the viewpoint of obtaining a highly crystalline GIS-type zeolite.
[0173] From the viewpoint of excellent economic efficiency in producing zeolite, the time for the hydrothermal synthesis is preferably 30 days or less, more preferably 20 days or less, and even more preferably 10 days or less.
[0174] In the hydrothermal synthesis step, the container for placing the mixed gel is not particularly limited as long as it is a commonly used container, but when the pressure in the container is increased at a predetermined temperature, or when the gas that does not inhibit crystallization is pressurized, it is preferred to place the mixed gel in a pressure-resistant container for hydrothermal synthesis.
[0175] The pressure-resistant container is not particularly limited, and various shapes such as a spherical shape, a vertically elongated shape, and a horizontally elongated shape may be used.
[0176] When the mixed gel in the pressure-resistant container is stirred, the pressure-resistant container is rotated in the vertical direction and / or the horizontal direction, preferably in the vertical direction.
[0177] When the pressure-resistant container is rotated in the vertical direction, the rotation speed is not particularly limited as long as it is in a generally used range, but is preferably 1 to 50 rpm, more preferably 10 to 40 rpm.
[0178] In the hydrothermal synthesis step, when the mixed gel is preferably stirred, there can be mentioned a method of using a vertically long container as a pressure-resistant container and rotating the container in the up-and-down direction.
[0179] [Separation / Drying Process]
[0180] After the hydrothermal synthesis step, the solid product and the liquid containing water are separated. The separation method is not particularly limited as long as it is a common method. Filtration, decantation, spray drying (rotary spray, nozzle spray and ultrasonic spray, etc.), drying using a rotary evaporator, vacuum drying, freeze drying or natural drying, etc. can be used. Separation can usually be carried out by filtration or decantation.
[0181] The separated product can be used directly or washed with water or a specified solvent. If necessary, the separated product can be dried.
[0182] The temperature for drying the separated product is not particularly limited as long as it is a normal drying temperature, and is usually room temperature to 150° C. or lower.
[0183] The atmosphere during drying is not particularly limited as long as it is an atmosphere commonly used, and an air atmosphere, an atmosphere to which an inert gas such as nitrogen or argon or oxygen is added is usually used.
[0184] [Firing process]
[0185] GIS type zeolite can be used after being calcined as needed. The calcination temperature is not particularly limited as long as it is a commonly used temperature. When it is desired to remove the organic structure directing agent, it is preferably 300°C or higher, more preferably 350°C or higher, because it can reduce the residual ratio. From the perspective of shortening the calcination time and improving the economic efficiency when manufacturing zeolite, it is more preferably 360°C or higher.
[0186] Since the crystallinity of zeolite tends to be maintained, the temperature is preferably less than 450°C, more preferably 420°C or lower, and even more preferably 400°C or lower.
[0187] The firing time is not particularly limited as long as it is a time that can fully remove the organic structure directing agent, and can be appropriately selected according to the firing temperature. Since there is a tendency to reduce the residual ratio of the organic structure directing agent, it is preferably 0.5 hours or more, more preferably 1 hour or more, and further preferably 3 hours or more.
[0188] Since the crystallinity of zeolite tends to be maintained, the time is preferably 10 days or less, more preferably 7 days or less, and even more preferably 5 days or less.
[0189] The firing atmosphere is not particularly limited as long as it is a commonly used atmosphere, and an air atmosphere, an atmosphere to which an inert gas such as nitrogen or argon or oxygen is added is usually used.
[0190] [Cation Exchange]
[0191] The GIS type zeolite can be subjected to cation exchange to obtain the desired cation type as required. Cation exchange can be performed using, but is not limited to, NH 4 NO 3 、LiNO 3 、NaNO 3 、KNO 3 , RbNO 3 , CsNO 3 、Be(NO 3 ) 2 、Ca(NO 3 ) 2 Mg(NO 3 ) 2 、Sr(NO 3 ) 2 ,Ba(NO 3 ) 2 or salts in which nitrate ions contained in the above nitrates are changed to halide ions, sulfate ions, carbonate ions, bicarbonate ions, acetate ions, phosphate ions or hydrogenphosphate ions; or acids such as nitric acid or hydrochloric acid.
[0192] The temperature for cation exchange is not particularly limited as long as it is a normal cation exchange temperature, and is usually room temperature to 100° C. or lower.
[0193] When separating the zeolite after cation exchange, the separation method is not particularly limited as long as it is a common method, and filtration, decantation, spray drying (rotary spray, nozzle spray and ultrasonic spray, etc.), drying using a rotary evaporator, vacuum drying, freeze drying, or natural drying, etc. can be used. Separation can usually be carried out by filtration or decantation.
[0194] The separated product can be used directly or washed with water or a specified solvent. If necessary, the separated product can be dried.
[0195] The temperature for drying the separated product is not particularly limited as long as it is a normal drying temperature, and is usually room temperature to 150° C. or lower.
[0196] The atmosphere during drying is not particularly limited as long as it is an atmosphere commonly used, and an air atmosphere, an atmosphere to which an inert gas such as nitrogen or argon or oxygen is added is usually used.
[0197] Furthermore, the ammonium-type zeolite can be converted into the proton-type zeolite by calcining the zeolite.
[0198] As the counter cations of the GIS-type zeolite of the present embodiment obtained by cation exchange, for example, cation exchange may be appropriately performed from the viewpoint of adjusting the amount of sodium as the counter cation, as described above.
[0199] The use of the GIS-type zeolite of this embodiment is not particularly limited, and it can be used, for example, as a separator or separation membrane for various gases and liquids, an electrolyte membrane for fuel cells, etc., a filler for various resin molded bodies, a membrane reactor, or a catalyst for hydrogen cracking, alkylation, etc., a catalyst carrier for loading metals, metal oxides, etc., an adsorbent, a desiccant, a detergent builder, an ion exchanger, a wastewater treatment agent, a fertilizer, a food additive, a cosmetic additive, etc.
[0200] Among the above, the GIS type zeolite of the present embodiment can be appropriately used as an adsorbent. That is, the adsorbent of the present embodiment includes the GIS type zeolite of the present embodiment. Since the adsorbent of the present embodiment is configured as described above, it can fully adsorb carbon dioxide, and the selectivity of carbon dioxide adsorption is higher than that of methane adsorption. Therefore, it can be particularly preferably used for the purpose of selectively removing carbon dioxide from natural gas, for example.
[0201] The adsorbent of the present embodiment is not particularly limited in its composition as long as it includes the GIS type zeolite of the present embodiment. Typical compositions include: Figure 2 Example shown. Figure 2 The adsorbent 1 of the present embodiment illustrated in the figure has filters 3 arranged at both the inlet side and the outlet side, and a plurality of zeolite particles 4 (GIS type zeolite of the present embodiment) arranged between the two filters 3, inside the container 2. As the filter 3, for example, a filter made of quartz can be used. For example, when the adsorbent 1 is used to remove carbon dioxide from natural gas, natural gas can be introduced from an upper pipeline, and after impurities are removed by the filter 3, carbon dioxide is further selectively adsorbed and removed by the zeolite particles 4, and methane-rich gas is taken out from the lower pipeline. The object supplied to the adsorbent is not limited to natural gas, and the internal structure of the adsorbent is not limited to Figure 2 Example shown.
[0202] (Separation method)
[0203] In the separation method of this embodiment, the adsorbent of this embodiment is used, and the adsorbent is selected from the group consisting of H 2 、N 2 , O 2, Ar, CO and hydrocarbons, and a mixture of at least two gases selected from the group consisting of CO 2 , H 2 O, He, Ne, Cl 2 NH 3 In this embodiment, it is preferred to select from N 2 , O 2 , CO and hydrocarbons, and separating a gas selected from the group consisting of CO 2 , H 2 One or more of the group consisting of O. The hydrocarbon is not particularly limited, and examples thereof include methane, ethane, ethylene, propane, propylene, 1-butene, 2-butene, 2-methylpropylene, dimethyl ether, and acetylene.
[0204] In the GIS type zeolite of the present embodiment, CO 2 The effective adsorption capacity is large, and physical adsorption without chemical bonds is observed. There is no particular limitation on the separation method using the GIS-type zeolite of the present embodiment, and a method with low energy and excellent economy during adsorbent regeneration is preferred. There is no particular limitation on the specific example of the method, but it is preferred to use any one of a pressure swing adsorption separation method, a temperature swing adsorption separation method, or a pressure swing-temperature swing adsorption separation method. The pressure swing adsorption separation method (PSA: Pressure Swing Adsorption) is a method in which the pressure during gas desorption is lower than the pressure during adsorption, and the difference between the adsorption amount at high pressure and the adsorption amount at low pressure is used to separate the gas. In addition, the temperature swing adsorption separation method (TSA: Thermal Swing Adsorption) is a method in which the temperature during gas desorption is higher than the temperature during adsorption, and the difference between the adsorption amount at low temperature and the adsorption amount at high temperature is used to separate the gas. In addition, a method of combining them is a pressure swing-temperature swing adsorption separation method (PTSA: Pressure and ThermlSwing Adsorption). These methods can be implemented under various known conditions.
[0205] It should be noted that the separation method of the present embodiment can be implemented as a method for producing a purified gas. That is, in the method for producing a purified gas of the present embodiment, an adsorbent comprising the GIS type zeolite of the present embodiment is used, and an adsorbent selected from the group consisting of H 2 、N 2 , O 2 , Ar, CO and hydrocarbons, and a mixture of at least two gases selected from the group consisting of CO 2 , H 2 O, He, Ne, Cl 2 NH3 Here, for example, in the case where methane and carbon dioxide are separated from a mixed gas containing methane and carbon dioxide in the form of carbon dioxide being adsorbed by an adsorbent, the purified gas in this embodiment may be methane or carbon dioxide. That is, the gas that is the adsorbate of the adsorbent in this embodiment and other gases can be recovered as the purified gas in this embodiment.
[0206] Example
[0207] The present embodiment is described in more detail by giving examples etc. below, but these examples are for illustration, and the present embodiment is not limited to the following examples. Those skilled in the art can make various changes to the following examples and implement them as the present embodiment, and the changes are included in the scope of the present invention as long as the specific conditions of the present embodiment are met.
[0208] [X-ray diffraction; crystal structure analysis]
[0209] X-ray diffraction was performed in the following procedure.
[0210] (1) The dried products obtained in each example and comparative example were crushed in an agate mortar as samples. 10 mass % of crystalline silicon (manufactured by Rare Metallic Co., Ltd.) was further added and mixed in an agate mortar until uniformity was achieved to prepare samples for structural analysis.
[0211] (2) The sample of (1) above was uniformly fixed on a non-reflective sample plate for powder, and the crystal structure was analyzed by X-ray diffraction under the following conditions.
[0212] X-ray diffraction apparatus (XRD): Powder X-ray diffraction apparatus "RINT2500" (trade name) manufactured by Rigaku Corporation
[0213] X-ray source: Cu tube (40kV, 200mA)
[0214] Measurement temperature: 25℃
[0215] Measuring range: 5~60°(0.02° / step)
[0216] Measuring speed: 0.2° / min
[0217] Slit width (scattering, divergence, light receiving): 1°, 1°, 0.15mm
[0218] (3) After the obtained X-ray diffraction spectrum is corrected for 2θ shift using the diffraction peak of crystalline silicon, data analysis is performed using XRD data analysis software "PDXL2" (software name, manufactured by Rigaku Corporation) with the setting value "α cutoff value" in the analysis software set to 3.00, and the 2θ value of the peak and its height are measured.
[0219] [CO 2 Adsorption amount and effective adsorption capacity; gas adsorption isotherm determination]
[0220] The gas adsorption isotherm measurement was performed in the following procedure.
[0221] (1) The dried product obtained in each of the Examples and Comparative Examples was used as a sample, and 0.2 g of the dried product was added to a 12 mm sample cell (manufactured by MicroMeritics).
[0222] (2) The sample put into the sample cell in (1) above was placed in a gas adsorption measuring device "3-Flex" (trade name) manufactured by Micro Meritics, and subjected to a heating vacuum degassing treatment at 250°C and 0.001 mmHg or less for 12 hours.
[0223] (3) The sample added to the sample cell after the treatment in (2) above was placed in a constant temperature circulating water at 25°C. After the temperature of the sample reached 25±0.2°C, liquefied carbon dioxide (manufactured by Sumitomo Seika Co., Ltd., purity 99.9% by mass or more) was used for measurement at an absolute pressure of 0.25 to a maximum of 760 mmHg. It should be noted that in the above measurement, the pressure was measured over time, and when the pressure change was less than 0.001% / 10 sec, it was determined that the saturated adsorption amount had been reached, and this was used as the CO pressure at 25°C. 2 Adsorption capacity (unit: cc / g).
[0224] (4) When the adsorbent is regenerated by heating, in order to measure the carbon dioxide adsorption at 180°C, the sample added to the sample cell after the treatment in (2) above is placed in a ring furnace, and after the temperature of the sample reaches 180±0.2°C, the measurement is performed using liquefied carbon dioxide (manufactured by Sumitomo Seika Co., Ltd., purity 99.9% by mass or more) at an absolute pressure of 0.25 to a maximum of 760 mmHg. It should be noted that in the above measurement, the pressure is measured over time, and when the pressure change is less than 0.001% / 10 sec, it is determined that the saturated adsorption has been reached, and this is used as the CO adsorption at 180°C. 2 Adsorption capacity (unit: cc / g). CO 2 Adsorption minus 180℃ CO 2The value obtained by the adsorption amount is taken as the effective adsorption capacity. It should be noted that, regarding the adsorption of carbon dioxide on GIS type zeolite, physical adsorption without chemical bonds was observed, and the same is true for desorption, and factors such as the difference between adsorption energy and desorption energy can be ignored. Therefore, the above effective adsorption capacity can be regarded as the same as the desorption amount of carbon dioxide during the heating regeneration treatment of zeolite for evaluation.
[0225] [Measurement of atomic number concentration and SAR of silicon, aluminum, phosphorus, titanium and zirconium]
[0226] Zeolite is thermally dissolved in an aqueous sodium hydroxide solution or aqua regia, and the concentrations of silicon, aluminum, phosphorus, titanium, and zirconium in the zeolite are measured by ICP-atomic emission spectrometry (hereinafter also referred to as "ICP-AES", SPS3520UV-DD manufactured by Seiko Instruments Co., Ltd.: device name) using an appropriately diluted liquid. The obtained atomic number concentrations of silicon and aluminum are converted into silicon oxide and aluminum oxide, and SAR is calculated.
[0227] [Determination of carbon atom content]
[0228] About 2 mg of the powder sample of the GIS type zeolite was weighed and the carbon atom content in the zeolite was measured by CHN elemental analysis (MT-6 manufactured by Yanaco Analytical Industry Co., Ltd.: device name). 2 In order to detect only the carbon atoms contained in the zeolite, the zeolite powder sample was placed in a sealed container, evacuated with a vacuum pump for more than 3 hours while being heated at 200°C, then taken out into the atmosphere and left to stand in the atmosphere for more than 24 hours before measurement and elemental analysis.
[0229] [Example 1]
[0230] 123.60 g of water, 1.44 g of sodium hydroxide (NaOH, manufactured by Wako Pure Chemical Industries, Ltd.), and sodium aluminate (NaAlO 2 , manufactured by Wako Pure Chemical Industries, Ltd.) and 21.68 g of colloidal silica (Ludox AS-40, solid content concentration 40% by mass, manufactured by Grace Co., Ltd.) were mixed and stirred for 1 hour to prepare a mixed gel. The composition of the mixed gel is α = SiO 2 / Al 2 O 3 =7.21, β = Na 2 O / Al 2 O 3 =1.90,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H2 O / Al 2 O 3 =379.33, ε = H 2 O / OH - =210.74, ζ = R / Al 2 O 3 = 0.00. The mixed gel was placed in a 200 mL stainless steel micro-bottle (manufactured by HIRO COMPANY) with a fluororesin inner cylinder, and hydrothermal synthesis was performed for 7 days at a stirring speed of 30 rpm and 135° C. in a stirring thermostatic bath (manufactured by HIRO COMPANY) that can rotate in the up and down direction of the micro-bottle. The product was filtered out and dried at 120° C. to obtain a powdered zeolite.
[0231] The XRD spectrum of the obtained zeolite is shown in Figure 1 The spectrum confirmed that the obtained zeolite was GIS type zeolite. In addition, no peaks derived from other zeolites or amorphous silica-alumina were observed, so it was evaluated as a high-purity GIS type zeolite. Regarding the peak intensity ratio obtained from the XRD pattern, A / B=0.89, B / C=16.8.
[0232] The concentrations of aluminum, silicon, phosphorus, titanium, zirconium, and sodium were measured by ICP-AES, and the silicon oxide-aluminum oxide ratio was calculated, and the result was SAR = 6.40. Phosphorus, titanium, and zirconium were not detected. Sodium was 7.4% by mass. The carbon atom concentration was measured by CHN analysis, but no carbon atoms were detected.
[0233] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 71.5 cc / g and 4.3 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 67.2 cc / g.
[0234] [Example 2]
[0235] Zeolite was synthesized in the same manner as in Example 1 except that water was 126.16 g, sodium hydroxide was 3.08 g, sodium aluminate was 3.84 g, and colloidal silica was 21.68 g. The composition of the mixed gel was α=SiO 2 / Al 2 O 3 =7.21, β = Na 2 O / Al 2 O 3 =1.90,γ=P 2 O 5 / Al 2 O 3 =0.0, δ = H2 O / Al 2 O 3 =386.58, ε = H 2 O / OH - =100.41, ζ = R / Al 2 O 3 = 0.00. The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.82, B / C = 23.5, SAR was 5.40, and no phosphorus, titanium, zirconium, or carbon atoms were detected. Sodium was 8.0 mass %.
[0236] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 65.2 cc / g and 3.7 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 61.5 cc / g.
[0237] [Example 3]
[0238] Zeolite was synthesized in the same manner as in Example 1 except that 6.0 g of 35% by mass tetraethylammonium hydroxide aqueous solution (manufactured by Aldrich) was added to 124.0 g of water, 0.88 g of sodium hydroxide, 3.28 g of sodium aluminate, and 21.64 g of colloidal silica, and the hydrothermal synthesis temperature was set to 130° C. The composition of the mixed gel was α=SiO 2 / Al 2 O 3 =7.20, β = Na 2 O / Al 2 O 3 =1.55,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =380.37, ε = H 2 O / OH - =169.0, ζ = R / Al 2 O 3 =1.15. The values were measured by the same method as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B=0.75, B / C=17.2, SAR was 5.40, and carbon atoms were 3.00% by mass. No phosphorus, titanium, or zirconium was detected. Sodium was 7.9% by mass.
[0239] The CO of the obtained GIS type zeolite 2When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 58.4 cc / g and 2.8 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 55.6 cc / g.
[0240] [Example 4]
[0241] 125.86 g of water, 0.86 g of sodium hydroxide, 1.65 g of sodium aluminate, and 24.80 g of water glass No. 3 (manufactured by Kishida Chemical Co., Ltd.) were mixed and stirred for 30 minutes to prepare a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =12.30, β = Na 2 O / Al 2 O 3 =6.05,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =774.24, ε = H 2 O / OH - =360.36, ζ = R / Al 2 O 3 = 0.00. The mixed gel was placed in a 200 mL stainless steel micro-bottle with a fluororesin inner cylinder and allowed to stand in a thermostatic bath at 130°C for 4 days for hydrothermal synthesis. The product was filtered and dried at 120°C to obtain a powdered zeolite.
[0242] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 1.16, B / C = 17.0, SAR was 4.25, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 8.3 mass %.
[0243] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 55.3 cc / g and 3.5 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 51.8 cc / g.
[0244] [Example 5]
[0245] Zeolite was synthesized in the same manner as in Example 1 except that 125.66 g of water, 0.66 g of sodium hydroxide, 1.65 g of sodium aluminate, and 24.80 g of water glass No. 3 were used. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =12.30, β = Na 2 O / Al 2 O 3 =5.80,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =773.76, ε = H 2 O / OH - =471.98, ζ = R / Al 2 O 3 =0.00.
[0246] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 1.05, B / C = 11.5, SAR was 4.60, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 8.1 mass %.
[0247] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 58.4 cc / g and 3.6 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 54.8 cc / g.
[0248] [Example 6]
[0249] Zeolite was synthesized in the same manner as in Example 1 except that 115.76 g of water, 0.62 g of sodium hydroxide, 1.65 g of sodium aluminate, and 20.16 g of water glass No. 3 were used. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =10.00, β = Na 2 O / Al 2 O 3 =5.00,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3=707.31,ε=H 2 O / OH - =460.00, ζ = R / Al 2 O 3 =0.00.
[0250] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.98, B / C = 11.2, SAR was 4.45, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 8.1 mass %.
[0251] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 56.2 cc / g and 3.5 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 52.7 cc / g.
[0252] [Example 7]
[0253] 120.00 g of water, 1.01 g of sodium hydroxide, 2.30 g of sodium aluminate, and 21.05 g of tetraethoxysilane (manufactured by Wako Pure Chemical Industries, Ltd.) were mixed and stirred for 60 minutes to prepare a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =7.21, β = Na 2 O / Al 2 O 3 =1.90,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =379.33, ε = H 2 O / OH-=210.81、ζ=R / Al 2 O 3 = 0.00. The mixed gel was placed in a 200 mL stainless steel microbottle with a fluororesin inner cylinder and allowed to stand in a thermostatic bath at 130°C for 4 days for hydrothermal synthesis. The product was filtered and dried at 120°C to obtain a powdered zeolite.
[0254] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.63, B / C = 15.9, SAR was 7.20, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 7.1 mass %.
[0255] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 71.2 cc / g and 5.5 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 65.7 cc / g.
[0256] [Example 8]
[0257] Zeolite was synthesized in the same manner as in Example 7 except that the amount of tetraethoxysilane was 17.52 g and the hydrothermal synthesis temperature was 135° C. The composition of the mixed gel was α=SiO 2 / Al 2 O 3 =7.21, β = Na 2 O / Al 2 O 3 =1.90,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =379.33, ε = H 2 O / OH-=210.81、ζ=R / Al 2 O 3 = 0.00. The mixed gel was placed in a 200 mL stainless steel microbottle with a fluororesin inner cylinder and allowed to stand in a thermostatic bath at 135°C for 4 days for hydrothermal synthesis. The product was filtered and dried at 120°C to obtain a powdered zeolite.
[0258] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.61, B / C = 13.3, SAR was 6.04, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 7.7 mass %.
[0259] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 67.6 cc / g and 5.4 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 62.2 cc / g.
[0260] [Example 9]
[0261] Zeolite was synthesized in the same manner as in Example 7 except that water was 140.56 g, sodium hydroxide was 1.71 g, sodium aluminate was 2.30 g, and tetraethoxysilane was 40.85 g. The composition of the mixed gel was α=SiO2 / Al 2 O 3 =14.00, β = Na 2 O / Al 2 O 3 =2.58,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =379.33, ε = H 2 O / OH - =120.00, ζ = R / Al 2 O 3 =0.00.
[0262] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 1.21, B / C = 24.8, SAR was 10.10, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 6.8 mass %.
[0263] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 70.9 cc / g and 8.2 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 62.7 cc / g.
[0264] [Comparative Example 1]
[0265] Based on the contents of Patent Document 3, 207.30 g of water, 8.78 g of sodium hydroxide, 16.4 g of sodium aluminate, and 248.3 g of water glass No. 3 were mixed and stirred for 15 minutes to prepare a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =12.39, β = Na 2 O / Al 2 O 3 =6.10,γ=P 2 O 5 / Al 2 O 3 =0.0, δ = H 2 O / Al 2 O 3 =197.86, ε = H 2 O / OH - =90.17, ζ = R / Al 2 O 3= 0.00. The mixed gel was placed in a 1000 mL stainless steel autoclave equipped with a fluororesin inner cylinder, and hydrothermally synthesized at 130°C for 5 days without stirring. The product was filtered and dried at 120°C to obtain a powdery zeolite.
[0266] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.67, B / C = 15.6, SAR was 4.10, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 8.0 mass %.
[0267] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 52.4 cc / g and 10.6 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 41.8 cc / g.
[0268] [Comparative Example 2]
[0269] Based on the contents of Non-Patent Document 1, 132.86 g of water, 15.66 g of sodium hydroxide, 7.2 g of sodium aluminate (manufactured by Alfa Aesar) and 25.56 g of colloidal silica (Ludox AS-40, solid content concentration 40% by mass) were mixed and stirred at room temperature for 24 hours to prepare a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =7.96, β = Na 2 O / Al 2 O 3 =10.75,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =371.79, ε = H 2 O / OH - =19.08, ζ = R / Al 2 O 3 = 0.00. The mixed gel was placed in a 200 mL stainless steel autoclave equipped with a fluororesin inner cylinder, and hydrothermally synthesized at 100°C for 7 days without stirring. The product was filtered and dried at 120°C to obtain a powdery zeolite.
[0270] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 1.13, B / C = 11.3, SAR was 2.60, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 8.6 mass %.
[0271] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 8.1 cc / g and 2.1 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 6.0 cc / g.
[0272] [Comparative Example 3]
[0273] Based on the contents of Non-Patent Document 3, 102.57 g of water, 2.45 g of sodium hydroxide (manufactured by Junsei Chemical Co., Ltd.), 1.15 g of sodium aluminate (manufactured by Showa Chemical Co., Ltd.), and 24.07 g of water glass (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed and stirred at N 2 The mixture was stirred at 1800 rpm for 24 hours under a 30° atmosphere to prepare a mixed gel. The composition of the mixed gel is α = SiO 2 / Al 2 O 3 =20.0, β = Na 2 O / Al 2 O 3 =14.00,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =840.00,ε=H 2 O / OH-=103.05、ζ=R / Al 2 O 3 = 0.00. The mixed gel was subjected to hydrothermal synthesis at 100°C for 24 hours while being stirred at 1000 rpm, and the product was filtered out and dried at 120°C to obtain a powdery GIS-type zeolite.
[0274] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.61, B / C = 11.4, SAR was 4.68, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 8.0 mass %.
[0275] The CO of the obtained GIS type zeolite 2When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 9.8 cc / g and 2.3 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 7.5 cc / g.
[0276] [Comparative Example 4]
[0277] Based on the contents of Non-Patent Document 3, zeolite was synthesized by the same method as in Comparative Example 3 except that 101.49 g of water, 1.90 g of sodium hydroxide, 1.15 g of sodium aluminate, and 26.48 g of water glass were mixed. The composition of the mixed gel was α=SiO 2 / Al 2 O 3 =22.0, β = Na 2 O / Al 2 O 3 =14.00,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =840.00,ε=H 2 O / OH-=132.63、ζ=R / Al 2 O 3 = 0.00. The product was filtered out and dried at 120°C to obtain powdery GIS type zeolite.
[0278] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.62, B / C = 11.3, SAR was 4.22, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 7.9 mass %.
[0279] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 10.2 cc / g and 3.0 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 7.2 cc / g.
[0280] [Comparative Example 5]
[0281] Based on the content of Patent Document 1, silicon oxide (SiO 2 , Fujifilm-Wako Pure Chemical Industries, Ltd.) 21.54g, aluminum oxide (Al 2 O 3 , Fujifilm-Wako Pure Chemical Industries, Ltd.) 5.97g, iron oxide (Fe 2 O 3, Fujifilm-Wako Pure Chemical Industries, Ltd.) 1.17g, titanium oxide (TiO 2 , manufactured by Fujifilm-Wako Pure Chemical Industries, Ltd.) 0.27g, calcium oxide (CaO, manufactured by Fujifilm-Wako Pure Chemical Industries, Ltd.) 0.21g, magnesium oxide (MgO, manufactured by Fujifilm-Wako Pure Chemical Industries, Ltd.) 0.06g, sodium hydroxide 0.03g, potassium hydroxide 0.21g, phosphorus oxide (P 2 O 5 , Fujifilm-Wako Pure Chemical Industries, Ltd.) 0.05 g and carbon powder (Strem Chemicals) 0.53 g were kneaded in an automatic mortar, and sodium carbonate (Na 2 CO 3 , Fujifilm-Wako Pure Chemical Industries, Ltd.) 17.6 g and mixed, and melted in an electric furnace at 1000°C for 1 hour. The melt was then cooled and pulverized, and 149.78 g of water was added to make H 2 O / Na 2 O in a molar ratio of 50 to prepare a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =6.12, β = Na 2 O / Al 2 O 3 =2.84,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =142.00、ε=H 2 O / OH - =1848.89, ζ = R / Al 2 O 3 = 0.00. The mixed gel was heated at 100°C for 24 hours in an autoclave, and the product was filtered out and dried at 120°C to obtain a powdery GIS type zeolite.
[0282] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B=0.65, B / C=10.2, SAR was 3.33, 0.12 wt% phosphorus and 0.03 wt% titanium were detected, and no zirconium or carbon atoms were detected. Sodium was 8.2 mass %.
[0283] The CO of the obtained GIS type zeolite 2When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 2.4 cc / g and 1.2 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 1.2 cc / g.
[0284] [Comparative Example 6]
[0285] Based on the content of non-patent document 6, 0.55 g of sodium aluminate, 0.35 g of sodium metasilicate (Na2SiO3, manufactured by Fujifilm-Wako Pure Chemical Industries, Ltd.), and 1.43 g of fumed silica (Aerosil300, manufactured by NIPPONAEROSIL) were mixed with 10 cc of 0.1 mol / L sodium hydroxide aqueous solution to obtain a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =8.0, β = Na 2 O / Al 2 O 3 =1.00,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =166.00、ε=H 2 O / OH-=550.00、ζ=R / Al 2 O 3 = 0.00. The mixed gel was placed in a stainless steel microbottle and heated at 200°C for 7 days to synthesize zeolite.
[0286] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.60, B / C = 11.0, SAR was 6.94, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 7.2 mass %.
[0287] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 3.2 cc / g and 1.5 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 1.7 cc / g.
[0288] [Comparative Example 7]
[0289] Based on the content of Patent Document 2, sodium metasilicate pentahydrate (Na 2 O 3 Si / 5H 2O, Aldrich) 18g and water 210.0g were mixed, and triethanolamine (C 6 H 25 NO 3 , CarlRoth GmbH) 127.1g, stirred at 600rpm for 30 minutes. A solution of 2.34g sodium hydroxide and 148.0g water was added to the stirred liquid, and stirred at 600rpm for 30 minutes at room temperature to obtain a mixed solution that does not contain Al. 1.134g of aluminum powder (Al, Wako Pure Chemical Industries, Ltd.) was added to a 1000mL stainless steel autoclave with a fluororesin inner cylinder, and the mixed solution was added. Hydrothermal synthesis was performed at 95°C for 5 days without stirring without aging time, and the product was filtered out and dried at 120°C to obtain a powdered zeolite.
[0290] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.75, B / C = 5.10, SAR was 4.60, phosphorus, titanium, and zirconium were not detected, carbon atoms were 13.5 mass %, and sodium was 3.5 mass %.
[0291] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 1.1 cc / g and 0.1 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 1.0 cc / g.
[0292] [Comparative Example 8]
[0293] Based on the contents of non-patent document 5, 189.90 g of water, 8.17 g of aluminum isopropoxide, 17.37 g of tetraethyl orthosilicate (manufactured by Aldrich) and 176.85 g of tetramethylammonium hydroxide pentahydrate (manufactured by Aldrich) as an organic structure directing agent were mixed and stirred for 30 minutes. After the stirred solution was kept at 0°C for 1 hour, it was stirred for 20 hours with a rotary shaker, heated at 120°C for 33 minutes, and cooled at 0°C for 15 minutes, thereby preparing a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =4.17, β = Na 2 O / Al 2 O 3 =0.0,γ=P 2 O 5 / Al 2 O 3 =0.0, δ = H 2 O / Al 2 O 3=253,ε=H 2 O / OH - =51.66, ζ = R / Al 2 O 3 = 4.78. The mixed gel was subjected to hydrothermal synthesis at 100°C for 13 days, and the product was filtered out and dried at 120°C to obtain a powdery zeolite.
[0294] The values were measured in the same manner as in Example 1. The peak intensity ratios obtained from the XRD pattern were A / B = 0.84, B / C = 6.15, SAR was 5.00, phosphorus, titanium, zirconium, and sodium were not detected, and the carbon atom content was 13.21% by mass.
[0295] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 0.3 cc / g and 0.1 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 0.2 cc / g.
[0296] [Comparative Example 9]
[0297] Based on the contents of Patent Document 4, 259.10 g of water, 0.98 g of sodium hydroxide, 20.50 g of sodium aluminate, and 310.4 g of water glass No. 3 were mixed and stirred for 45 minutes to prepare a mixed gel. The composition of the mixed gel is α=SiO 2 / Al 2 O 3 =12.00, β = Na 2 O / Al 2 O 3 =3.00,γ=P 2 O 5 / Al 2 O 3 =0.00, δ = H 2 O / Al 2 O 3 =200.00,ε=H 2 O / OH - =1009.8, ζ = R / Al 2 O 3 = 0.00. The mixed gel was placed in a 1000 mL stainless steel autoclave equipped with a fluororesin inner cylinder, and hydrothermally synthesized at 110°C for 2 days without stirring. The product was filtered and dried at 120°C to obtain a powdery zeolite.
[0298] 1 g of the obtained zeolite was added to 500 mL of 0.1 N potassium nitrate aqueous solution and stirred at 400 rpm for 3 hours at 60 ° C. The product was filtered out and dried at 120 ° C to obtain a powdered zeolite in which a part of the cations were exchanged for potassium. The diffraction peak of (1 0 1) is 12.74°, the diffraction peak of (3 0 1) is 28.52°, and the diffraction peak of (5 0 1) is 47.08°. All of them are not in the appropriate range of the diffraction peaks obtained by GIS in this technology, and the crystal structures are different. When the ratio of the diffraction peak heights is calculated from these diffraction peaks, (1 0 1) / (3 0 1)=0.67, (3 0 1) / (5 0 1)=15.0.
[0299] SAR was 4.10, phosphorus, titanium, zirconium and carbon atoms were not detected, and sodium was 0.3 mass%.
[0300] The CO of the obtained GIS type zeolite 2 When the adsorption isotherm was measured, the adsorption amounts at 25°C and 180°C and 760 mmHg were 67.5 cc / g and 28.8 cc / g, respectively, and the effective adsorption capacity based on the temperature difference between 25°C and 180°C was 38.7 cc / g.
[0301] [Table 1]
[0302]
[0303] α to ε in Table 1 represent the following molar ratios.
[0304] α=SiO 2 / Al 2 O 3 ,
[0305] β=(M1 2 O+M2O) / Al 2 O 3 (Here, M1 represents an alkali metal, and M2 represents an alkaline earth metal),
[0306] γ=P 2 O 5 / Al 2 O 3 ,
[0307] δ=H 2 O / Al 2 O 3 ,
[0308] ε=H 2 O / OH - ,
[0309] ζ=R / Al 2 O 3(R represents an organic structure directing agent.)
[0310] This application is based on the Japanese patent application (Japanese Patent Application No. 2020-130309) filed on July 31, 2020, the contents of which are incorporated herein by reference.
[0311] Industrial Applicability
[0312] The GIS type zeolite of the present invention has industrial applicability as a separator and separation membrane for various gases and liquids, an electrolyte membrane for fuel cells, etc., a filler for various resin molded bodies, a membrane reactor, or a catalyst for hydrogen cracking, alkylation, etc., a catalyst carrier for loading metals, metal oxides, etc., an adsorbent, a desiccant, a detergent builder, an ion exchanger, a wastewater treatment agent, a fertilizer, a food additive, a cosmetic additive, etc.
[0313] Explanation of symbols
[0314] 1. Adsorbent
[0315] 2 Containers
[0316] 3 Filters
[0317] 4 Zeolite particles
Claims
1. A GIS type zeolite having a carbon atom content of 4 mass % or less and satisfying at least one of the following conditions (i) and (ii): (i) the silicon oxide-aluminum oxide ratio is 6.04 or more, and in a spectrum obtained by X-ray diffraction, when the peak heights near 2θ=12.45° and near 2θ=28.07° are denoted as A and B, respectively, 0.62≤A / B; (ii) The silicon oxide-aluminum oxide ratio is 4.23 or more, and in a spectrum obtained by X-ray diffraction, when the peak heights near 2θ=28.07° and near 2θ=46.04° are represented by B and C, respectively, 13.3≤B / C.
2. The GIS type zeolite according to claim 1, comprising silica-alumina.
3. The GIS type zeolite according to claim 1 or 2, comprising H and an alkali metal element as counter cations.
4. The GIS type zeolite according to claim 1 or 2, wherein In the condition (i), the silicon oxide-alumina ratio is 6.04 to 20, and in the condition (ii), the silicon oxide-alumina ratio is 4.23 to 20.
5. The GIS type zeolite according to claim 4, wherein In the condition (i), the silicon oxide-alumina ratio is 6.04 to 15, and in the condition (ii), the silicon oxide-alumina ratio is 4.80 to 15.
6. The GIS type zeolite according to claim 1 or 2, wherein 0.62≤A / B≤2.
00.
7. The GIS type zeolite according to claim 1 or 2, wherein 13.3≤B / C≤35.
0.
8. The GIS type zeolite according to claim 7, wherein 15.7≤B / C≤35.
0.
9. The GIS type zeolite according to claim 1 or 2, wherein The effective adsorption capacity is 42 cc / g or more, and the effective adsorption capacity is the difference between the saturated adsorption capacity of CO2 of the GIS type zeolite at 25°C and the saturated adsorption capacity of CO2 at 180°C.
10. The GIS type zeolite according to claim 9, wherein The effective adsorption capacity is greater than 48 cc / g.
11. The GIS type zeolite according to claim 1 or 2, wherein In the spectrum obtained by X-ray diffraction, the half-value width of the peak near 2θ=12.45° was less than 0.45 degrees.
12. The GIS type zeolite according to claim 1 or 2, wherein In the spectrum obtained by X-ray diffraction, the half-value width of the peak near 2θ=28.07° was 0.80 degrees or less.
13. The GIS type zeolite according to claim 1 or 2, wherein In the spectrum obtained by X-ray diffraction, the half-value width of the peak near 2θ=46.04° was less than 0.95 degrees.
14. The GIS type zeolite according to claim 3, wherein The content of the alkali metal element is 0.6 mass % or more and 33 mass % or less based on the total amount of the GIS-type zeolite.
15. The GIS type zeolite according to claim 3, wherein The alkali metal element is sodium. 16 . An adsorbent comprising the GIS-type zeolite according to claim 1 .
17. A separation method, wherein: Using the adsorbent described in claim 16, one or more gases selected from the group consisting of CO2, H2O, He, Ne, Cl2, NH3 and HCl are separated from a mixture of two or more gases containing one or more gases selected from the group consisting of H2, N2, O2, Ar, CO and hydrocarbons.
18. The separation method according to claim 17, wherein: The gas separation is performed by a pressure swing adsorption separation method, a temperature swing adsorption separation method or a pressure swing-temperature swing adsorption separation method.
19. A method for producing a purified gas, wherein: Using the adsorbent described in claim 16, one or more gases selected from the group consisting of CO2, H2O, He, Ne, Cl2, NH3 and HCl are separated from a mixture of two or more gases containing one or more gases selected from the group consisting of H2, N2, O2, Ar, CO and hydrocarbons.
20. The method for producing a purified gas according to claim 19, wherein: The gas separation is performed by a pressure swing adsorption separation method, a temperature swing adsorption separation method or a pressure swing-temperature swing adsorption separation method.
21. The method for producing a GIS type zeolite according to any one of claims 1 to 15, comprising the following steps: A process for preparing a mixed gel, the mixed gel comprising a silicon oxide source containing silicon, an aluminum source containing aluminum, an alkali source containing at least one selected from an alkali metal (M1) and an alkaline earth metal (M2), and water; and The hydrothermal synthesis step is to hydrothermally synthesize the mixed gel at a temperature of 80°C to 145°C. In the mixed gel obtained in the preparation process, SiO2 / Al2O3 is 3.0 or more and 70.0 or less, (M12O+M2O) / Al2O3 is 15.0 or less, and H2O / OH - It is greater than 169.0 and less than 480, and H2O / Al2O3 is greater than 270 and less than 780.
22. The method for producing GIS type zeolite according to claim 21, wherein: In the mixed gel obtained in the preparation step, (M12O+M2O) / Al2O3 is greater than or equal to 1.65 and less than or equal to 10.
0.
23. The method for producing GIS type zeolite according to claim 21 or 22, wherein: In the mixed gel obtained in the preparation step, P2O5 / Al2O3 is greater than or equal to 0 and less than or equal to 0.
4.
24. The method for producing GIS type zeolite according to claim 21 or 22, wherein: In the mixed gel obtained in the preparation step, the organic structure directing agent R / Al2O3 is 4 or less.
25. The method for producing a GIS type zeolite according to claim 21 or 22, wherein: The preparation process of the mixed gel comprises: A mixing step of mixing a silicon oxide source, an aluminum source, an alkali source, water, and, if necessary, an organic structure directing agent; and a aging step of aging the mixture obtained in the mixing step, The total time of the mixing step and the aging step is 20 minutes to 6 hours.
26. The method for producing GIS type zeolite according to claim 21 or 22, wherein: In the hydrothermal synthesis step, the hydrothermal synthesis time is more than 24 hours.
Citation Information
Patent Citations
Production of zeolite composition
JP1994340417A
Method for forming an aluminosilicate-zeolite layer on a metal substrate, coated substrate and its use
JP2012519148A
Game machine
JP2020130309A
GIS zeolite
WO2018110559A1
GIS-type zeolite
WO2019202933A1